Are posttraumatic stress disorder (PTSD) and complex-PTSD distinguishable within a treatment-seeking sample of Syrian refugees living in Lebanon?. (16th April 2018) - Hyland, P.; Ceannt, R.; Daccache, F.; Abou Daher, R.; Sleiman, J.; Gilmore, B.; Byrne, S.; Shevlin, M.; Murphy, J.; Vallières, F.
Abstract : Background: The World Health Organization will publish its 11 th revision of the International Classification of Diseases (ICD-11) in 2018. The ICD-11 will include a refined model of posttraumatic stress disorder (PTSD) and a new diagnosis of complex PTSD (CPTSD). Whereas emerging data supports the validity of these proposals, the discriminant validity of PTSD and CPTSD have yet to be tested amongst a sample of refugees. Methods: Treatment-seeking Syrian refugees ( N  = 110) living in Lebanon completed an Arabic version of the International Trauma Questionnaire ; a measure specifically designed to capture the symptom content of ICD-11 PTSD and CPTSD. Results: In total, 62.6% of the sample met the diagnostic criteria for PTSD or CPTSD. More refugees met the criteria for CPTSD (36.1%) than PTSD (25.2%) and no gender differences were observed. Latent class analysis results identified three distinct groups: (1) a PTSD class, (2) a CPTSD class and (3) a low symptom class. Class membership was significantly predicted by levels of functional impairment. Conclusion: Support for the discriminant validity of ICD-11 PTSD and CPTSD was observed for the first time within a sample of refugees. In support of the cross-cultural validity of the ICD-11 proposals, the prevalence of PTSD and CPTSD were similar to those observed in culturally distinct contexts.